Lukiolaisten saksan kielen määräisen artikkelin funktion hallinta - Penttinen, Esa Martti (Yliopistopaino, 1996)
Zsfassung in engl. Sprache u.d.T.: The mastering of the definite article in Geman by senior high school students
Zugl.: Helsinki, Univ., Diss., 1996
Keywords: Hochschulschrift